Study Management to Improve the Motivation of Educators Through Merdeka Belajar - Budi Tri Cahyono (al-fikrah: Jurnal Manajemen Pendidikan, 2022)
: The role of educators is very important in the teaching and learning process because the final results obtained by students determine the quality and quantity of learning. The role of educators is in charge of creating learning conditions in the classroom that are not monotonous, only listening, but learning that has innovation for the teaching and learning process. The purpose of this study is to explore the implementation of increasing educator motivation in learning using independent learning methods at Budi Utomo Middle School. The research method used is to collect data through the distribution of instruments and in-depth interviews with educators including the principal. The results obtained with the independent learning model of learning are 1. Reducing the burden on teachers, 2. Simplifying lesson plans, 3 Creating Received: 13-01-2022; Revised: 19-06-2022; Accepted: 25-06-2022 2 AL-FIKRAH, Volume X Nomor 1, Juni 2022 fun learning, 4. Improving the competence of educators. This aims to provide convenience for educators when carrying out the learning process with face-to-face meeting conditions as much as 50%, so that learning arrangements are needed with time divided into 3 stages each day. The demands of educator motivation are needed considering that learning activities and innovations in teaching need to be done to overcome boredom. From the explanation above, it is concluded that the freedom to plan the teaching and learning process is determined by educators to express creative and innovative ideas. With the qualitative method, the motivation of educators is expected to grow from the strength of internal and external encouragement in order to realize optimal learning. From the explanation above, it can be concluded that the freedom to plan the teaching and learning process is determined by educators for creative and innovative ideas.